Problèmes de structure dans les Andes. De la parenté, de la polygynie et des moitiés à Cuzco - R. Tom Zuidema (Journal de la Société des Américanistes)
Problems of structure in the Andes. Kinship, polygyny and moieties in Cuzco. Lévi-Strauss, in articles written in 1983, poses the problem of multiple choices, with different advantages, of kin relationships between a ruler and his subjects. He takes as a first example of analysis the Heian court in Japan of the eleventh century. A comparable example had been given by van Wouden in 1956 from the landscape of Kodi on the island of Sumba, Indonesia, and Lévi-Strauss (1958 [1956]) himself had referred before to that of the Bororo, South America. Taking three aspects of the problem as discussed by Lévi-Strauss, I demonstrate the importance of these in the case of the Inca empire, Peru, and illustrate them with examples taken from here.